Nursing, Midwifery and Health Officer Programs Undergraduate Students’ Attitudes towards Their Future Career: Motivating/Demotivating Professional Characteristics and Career Preferences (Annals of Medical Research, 2021)
None
Keywords: Nursing, midwifery, education, values, career preferences